Advances and Challenges in Structural Engineering : Proceedings of the 2nd GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 -- The Official International Congress of the Soil-Structure Interaction Group in Egypt (SSIGE) /: Proceedings of the 2nd GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2018 -- The Official International Congress of the Soil-Structure Interaction Group in Egypt (SSIGE). (2018) - Unknown
No abstract available